2006
DOI: 10.1002/ca.20361
|View full text |Cite
|
Sign up to set email alerts
|

The anatomic relationships of the axillary nerve and surgical landmarks for its localization from the anterior aspect of the shoulder

Abstract: The axillary nerve has long been known to be one of the nerves vulnerable to damage during shoulder arthroscopic and open surgical procedures. The relationship of the axillary nerve to the shoulder capsule and the subscapularis muscle has not been well defined in orthopedic literature. This descriptive anatomical study aimed to present the course and the relations of the axillary nerve with neighboring neurovascular structures and the shoulder capsule and to define anatomical landmarks and regions that can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 11 publications
2
32
1
1
Order By: Relevance
“…The mean distance between the tip of anteromedial aspect of the coracoid process and the medial edge of the subscapularis muscle was measured to be 2.5 cm [12].…”
Section: Discussionmentioning
confidence: 99%
“…The mean distance between the tip of anteromedial aspect of the coracoid process and the medial edge of the subscapularis muscle was measured to be 2.5 cm [12].…”
Section: Discussionmentioning
confidence: 99%
“…However, a disadvantage of this approach is that it is associated with high incidence of axillary nerve injury. [17][18][19] Axillary nerves are in fact one of the most commonly injured nerves during shoulder-related surgeries. 20) Gardner et al 13) reported that the axillary nerve is positioned on average 63.3 mm lateral to the acromion and 35.5 mm posterior to the greater tuberosity of the humerus.…”
Section: Discussionmentioning
confidence: 99%
“…In the superior part, the subacromial space is located by following the incision along the lateral edge of the conjoint tendon to the tip of the coracoid process and then continuing along or across the front edge of the coracoacromial ligament up to its acromial footprint. For the inferior part, it must be remembered that the lower dead end of the subdeltoid bursa is located above the axillary nerve around the humerus [11]. Thus, as long as we remain in the bursa, there is no risk for the nerve.…”
Section: Layer 2: Incision Of the Clavipectoral Fasciamentioning
confidence: 99%
“…11 Location of suture under humeral osteotomy area with prosthesis in place in lesser tuberosity osteotomy (cadaveric right shoulder); 52×34 mm (300×300 DPI) Fig. 12 Final "corner buttress" in lesser tuberosity osteotomy (cadaveric right shoulder): a bony fragment, b subscapularis tendon, c bicipital groove (empty), d conjoint tendon; 52×34 mm (300×300 DPI) through the insertion of the latissimus dorsi as base, the conjoint tendon as lateral side and the pectoralis minor as medial side [11].…”
Section: Management Of the Rotator Intervalmentioning
confidence: 99%
See 1 more Smart Citation